Nigeria rural economic survey : consolidated report of crop estimation surveys 1968/68 to 1970/71 - Agricultral Statistics Unit (Lagos, Nigeria : Federal Office of Statistics, 1972)
This is the fourth in the series of crop estimation surveys reports since the expanded programme of the Rural Economic Survey was launched by the Federal Office of Statistics in 1963
osc 05/04/2019
Arch
Keywords: Crop - Economics; Nigeria